Reevaluation of the Incidence of Thromboembolic Complications in Congenital Factor XII Deficiency - Zeerleder, S.; Schloesser, M.; Redondo, M.; Wuillemin, W. A.; Engel, W.; Furlan, M.; Lämmle, B. (Thrombosis and Haemostasis, 1999)
To further elucidate the debated role of hereditary FXII deficiency as a thrombophilic risk factor this follow-up study on 65 subjects out of 12 Swiss families was undertaken (follow-up: 6 yrs). Fifteen severely FXII deficient subjects (FXII:C < 1%), 35 partially FXII deficient subjects (FXII:C ≥ 1-59%), 10 with normal FXII values (FXII:C ≥ 70%), and 5 non-classifiable subjects (FXII:C ≥ 60-69%) were reevaluated. Eight subjects (4 severely and 3 partially FXII deficient, 1 non-classifiable) were newly enrolled. Four instances of deep vein thrombosis, one superficial vein thrombosis and one myocardial infarction were noted in 2 out of 19 severely FXII deficient subjects during a total life-time period of 866.6 patient-years. In 38 partially FXII deficient subjects (1862.8 patient-years) one ischemic cerebrovascular stroke and one superficial vein thrombosis were recorded in 2 individuals. The 10 subjects with normal FXII values (498.2 patient-years) remained thrombosis-free. One superficial vein thrombosis occurred in an unclassifiable woman. None of the 3 different FXII gene defects revealed in our patients was specifically associated with thromboembolic complications. Kaplan-Meier analysis of thrombosis-free survival suggests that hereditary partial (and probably severe) FXII deficiency does not constitute a thrombophilic condition.
Keywords: Factor XII deficiency; thromboembolic disease; factor XII gene mutations; thrombophilia